Pengaruh Jumlah Anggota, Jumlah Simpanan, Jumlah Modal dan Jumlah Pembiayaan Murabahah terhadap Sisa Hasil Usaha Koperasi Syariah Benteng Mikro Indonesia Tahun 2018-2022 - Prayoga, Deni; Amaliyah, Amaliyah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to analyze the influence of the number of members, the amount of savings, the amount of capital and Murabahah financing on the profit of the Koperasi Syariah Benteng Mikro Indonesia. This study of research uses a quantitative approach. In this study using monthly time series data from January 2018-December 2022 with a total sample of 60 samples. The analysis technique used is descriptive statistical test, multiple linear regression test and hypothesis testing using data processing applications such as E-Views 10 and Microsoft Excel. The results showed that partially, the number of members and amount of capital had no effect on profit of koperasi syariah benteng mikro Indonesia, amount of savings had a positive effect on profit of koperasi syariah benteng mikro Indonesia while the murabahah financing had a negative effect on profit of koperasi syariah benteng mikro Indonesia. Simultaneously the number of members, the amount of savings, the amount of capital and murabahah financing have a significant effect on profit of koperasi syariah benteng mikro Indonesia.